THE MANIFESTATION OF LAW IN THE ENFORCEMENT OF HUMAN RIGHTS IN INDONESIA: Legal Review of the Role of Komnas HAM in Aceh - Zi, Fairuzi; M. Yunus, Fakhrurrazi; Amri, Aulil (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2026)
Although human rights are considered basic rights that are not determined by social views or state legitimacy and are given to every individual from birth, in the context of Indonesia, even though Komnas HAM was established through Presidential Decree No. 50 of 1993 to protect human rights, its implementation still faces various challenges. One of the main problems is the lack of optimisation in the enforcement of human rights. This raises questions about the extent of the state's commitment to protecting human rights and its efforts to strengthen law enforcement mechanisms. The results of the study show that although Indonesia has adequate legal instruments to guarantee human rights, their implementation in the field still leaves gaps. In this study, the author uses qualitative methods with a field research and document analysis approach. The results of this study show that the manifestation of human rights in the Indonesian legal system is realised through the strengthening of regulations, the optimisation of mechanisms for affirming the role and authority of Komnas HAM, and improved coordination between law enforcement agencies.